Agonopterix guanchella Buchner, sp. n., a new species of Depressariidae from Canary Islands (Spain) (Lepidoptera: Depressariidae) - P. Buchner (SHILAP, 2022)
Agonopterix guanchella Buchner, sp. n. is described. It has been collected from three different places, all in Gran Canaria, Canary Islands, Spain. The adult and genitalia of both sexes of the new species and some similar species are illustrated. Hostplant is unknown so far, and a species closely related to it could not be detected.